The anatomy of serious further offending - Nash, Mike (Oxford University Press, 2008)
The nature and extent of serious further offences -- Back to basics-understanding offending behaviour -- Risk, dangerousness, and serious further offending -- Organizational structures-MAPPA and NOMS -- Inquiry culture-moving forward or process compliance? -- Failure and blame-learning lessons from elsewhere -- Serious further offending-types, reviews, and research -- SFO inquiries-opening Pandora's box -- Conclusion